AB0154 Radon therapy ameliorates disease progression and prolongs survival in TNF-transgenic mice. (23rd January 2014) - Janko, C.; Pauthner, M.; Baum, W.; Schorn, C.; Dobias, H.; Moder, A.; Schett, G.; Herrmann, M.
Abstract : Background: Radon therapy as alternative therapy for rheumatic diseases in curative tunnels such as the Heilstollen Bad Gastein in Austria has been reported to reduce pain and amount of drug usage [1, 2]. Inhaled radon remains in the body as decaying radioactive radon progeny, and exhibits analgesic and anti-inflammatory effects [3]. In the Heilstollen the patients usually receive mean radon doses of 44.000 Bq/m 3 air (dependent on the weather conditions). Objectives: Placebo effects of radon treatment at a health resort (caused by excitement, caring by the physicians) are discussed to contribute to clinical improvement of rheumatic diseases. To exclude placebo effects we analysed benefits of the radon therapy in an animal experiment performed under controlled conditions. Mice over-expressing human TNF-α that develop poly-arthritis served as animal model for rheumatoid arthritis. Methods: Gaseous radon from water of radon galleries of Bad Gastein, Austria, was prepared using an evaporation system. In addition to the breathing air the drinking water of the animals contained radon. The dosimetry was performed by liquid scintillation with radon enrichment on an activated carbon matrix. TNF tg (n=10) and wild type (n=7) mice were 12 x exposed to radon in 3 weeks for 3 hours per day. Mock treated TNF tg (n=11) and wild type mice (n=7) served as controls. The course of the disease was monitored by measurements of body weight, grip strength and mortality. All analyses were performed by two researchers blinded to the treatment conditions the mice had received. Results: The mean daily radon doses applied to the mice were 119213±39113 Bq/m 3 by inhalation. The drinking water contained 800-900 Bq/l. TNF tg mice showed severe illness marked by reduced body weight and decreasing grip strength compared to wild type controls. After treatment with radon TNF tg mice showed an improved body constitution and movement activity, measured by body weight and grip strength. Improvements continued until death of the mice. Interestingly, the TNF tg mice treated with radon showed an increased survival compared to mock treated TNF tg control mice. Conclusions: Radon therapy ameliorates the inflammatory processes responsible for the arthritogenic activity of human TNF in mice. The overall radon dosis applied to the mice is in the same range as during the treatment of patients in the Heilstollen Bad Gastein/Austria. References: Falkenbach A, Kovacs J, Franke A, Jörgens K, Ammer K., Radon therapy for the treatment of rheumatic diseases – review and meta-analysis of controlled clinical trials. Rheumatol Int. 2005; 25:205-10. Franke A, Reiner L, Pratzel HG, Franke T, Resch KL., Long-term efficacy of radon spa therapy in rheumatoid arthritis – a randomized, sham-controlled study and follow-up, Rheumatology (Oxford). 2000; 39:894-902. Shehata M, Schwarzmeier JD, Hilgarth M, Demirtas D, Richter D, Hubmann R, Boeck P, Leiner G, Falkenbach A., Effect of combined spa-exercise therapy on circulating TGF-beta1 levels in patients with ankylosing spondylitis., Wien Klin Wochenschr. 2006;118:266-72. Disclosure of Interest: None Declared